Measuring national financial development: indexes and methods - T. Ph.T. Duong (Publishing House of the State University of Management, 2021)
Financial development of a country is a broad concept and can be measured in different ways. The article presents the indicators of financial development applicable for the development of the Financial Development Index (FDI) of a particular country. Financial development index could be used to rank and compare the level of financial development among countries or to test the relationship between financial development and economic growth. The paper points out the advantages and limitations of several methods including standardized method, Principle Component Analysis (PCA) method, Data Envelopment Analysis (DEA) method. The author also suggests to use Data Envelopment Analysis as an updated and advanced method to construct Financial Development Index. It is expected that this method will strengthen the quantitative approach in the research of financial development and economic growth.